Price setting transactions and the role of denominating currency in FX markets - Richard Friberg; Fredrik Wilander (Sveriges Riksbank, 2007)
This report, commissioned by Sveriges Riksbank, examines the role of currency denomination in international trade transactions. It is divided in two parts. The first part consists of a survey of the price setting and payment practices of a large sample of Swedish exporting firms. The second part analyzes payments data from the Swedish settlement reports from 1999-2002. We examine whether invoicing patterns of Swedish and European companies changed following the creation of the EMU and how the currency denomination of exports differ from that of imports. Finally we consider the possibility that changes in invoicing patterns are correlated with changes in nominal exchange rates. Our main finding is that the same currency to a large extent is used for price setting, invoicing and payment for exports to third parties. We also find that the currency of the customer is the most used and that the euro is replacing the Swedish krona both in transactions with EMU-member countries but outside the EMU. Finally we find some evidence of a weak correlation between aggregate changes in invoicing patterns and changes in the trade weighted exchange rate over the period 1999-2002.
Keywords: F31; F41; G32; 330; invoicing currency; exchange rate pass-through; price setting currency; exchange rate exposure; nominal rigidity; Import; Export; Konditionen; Internationaler Zahlungsverkehr; Währungsrisiko; Währung; Eurozone; Schweden